Batak Christian Protestant Church's View Concerning Ecology - Hamonangan, Ranto Praja; Gultom, Martin (Institut Agama Kristen Negeri Manado, 2021)
This paper examines a discussion about ecology focus on Batak Christian Protestant Church's view and action. The study's reason is based on what the church said about ecological problems in their faith declaration. Furthermore, looking Batak Christian Protestant Church (HKBP) litigates connected to ecological action case in Indonesia. Methodology in this research is literary, looking at the book, internet, and faith confession of the HKBP. Gathering the data and then analyze is the approach used to discuss the issue. This study traced that the HKBP has mentioned ecology in their faith confession. In their view, HKBP argues that God created man in his residence and place of work in this world (Gen. 2:5-15). Therefore, they oppose any environmentally damaging activities, such as burning and cutting down trees in the forest or wilderness (Deuteronomy 5: 20; 19-20). This creed is based on the Word of God as recorded in the scriptures. They also have been activated to protect nature, for example: develop livestock waste into alternative energy (biogas); planting trees in Peak Dolok, Balige North Sumatera; statings local wisdom. Christianity realizes that ecology issues are also part of their problems. What has been done by the HKBP be a positive thing. This action is a good activity for Christianity in Indonesia. Even though we cannot deny the ecology problem is our common problem.